2015
DOI: 10.9738/intsurg-d-14-00184.1
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effect of Dexmedetomidine Against Postoperative Intra-abdominal Adhesions in Rats

Abstract: This study aimed to determine the possible preventive effects of dexmedetomidine on postoperative intra-abdominal adhesions. Dexmedetomidine is a highly selective and potent α2 adrenergic agonist with sedative, analgesic, anxiolytic, sympatholytic, hemodynamic, and diuretic properties. In recent years, investigations have shown that dexmedetomidine possesses secondary antioxidant and also anti-inflammatory effects. Thirty Wistar albino male rats were randomized and divided into 3 groups of 10 animals each: gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Since then, a growing number of research articles have aimed at investigating other possible applications, including use as a protective agent for I/R injury in various organs including the rat skeletal muscle, intestines, heart, kidneys, overs, lungs and liver. [6][7][8][9][10][29][30][31] In addition, in other studies, the beneficial effects of DEX on liver injury have been analyzed under different experimental conditions including hepatic ischemia-reperfusion injury, 30,31 obstructive jaundice, 13 trinitrobenzene sulfonic acid (TNBS)-induced inflammatory bowel disease, 32 acid-induced acute lung injury, 33 and experimental sepsis models. 34 Sahin et al 30 investigated the possible protection of DEX against IR-induced liver injury in rats and claimed that administration of DEX to the IR group reduced the MDA level while increasing the SOD, CAT, GSH, and GSH-Px activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, a growing number of research articles have aimed at investigating other possible applications, including use as a protective agent for I/R injury in various organs including the rat skeletal muscle, intestines, heart, kidneys, overs, lungs and liver. [6][7][8][9][10][29][30][31] In addition, in other studies, the beneficial effects of DEX on liver injury have been analyzed under different experimental conditions including hepatic ischemia-reperfusion injury, 30,31 obstructive jaundice, 13 trinitrobenzene sulfonic acid (TNBS)-induced inflammatory bowel disease, 32 acid-induced acute lung injury, 33 and experimental sepsis models. 34 Sahin et al 30 investigated the possible protection of DEX against IR-induced liver injury in rats and claimed that administration of DEX to the IR group reduced the MDA level while increasing the SOD, CAT, GSH, and GSH-Px activities.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Moreover, preclinical studies on DEX have indicated that DEX could be a good option for treating T cell-mediated liver injury, 11 and it has beneficial effects on the liver in experimental liver injury models including ischemia-reperfusion and obstructive jaundice. 12,13 It was concluded that these effects of DEX might also be due to its antioxidant and anti-inflammatory activities.…”
mentioning
confidence: 99%
“…Also, earlier studies were reported that dexmedetomidine decreased TNF-α and IL-6 concentrations in rats with sepsis [13,16] and alleviated in ammation in a rat model with spinal cord injury [7]. Furthermore, it signi cantly decreased the development of postoperative intraabdominal adhesions in rats with abdominal surgery [17]. This anti-in ammatory effect of dexmedetomidine was demonstrated also in clinical trials, where its administration postoperatively to patients requiring sedation and mechanical ventilation was associated with decreased concentrations of IL-6 levels [11].…”
Section: Discussionmentioning
confidence: 90%
“…The adhesion formation process has been explored in different ways and can be divided into four stages: an in ammatory post-injury stage, a brin dissolving stage, a brous band stage, and a phagocytic and remodeling stage [22][23][24]. Many studies have determined that in ammatory responses play an important role in the formation of adhesions [25,26]. Wei et al [27] reported that gallic acid reduces adhesions formation in rats by inhibiting in ammatory reactions.…”
Section: Discussionmentioning
confidence: 99%